Reflection on IIUM philosophy of education in a historical context - Shogar, Ibrahim (Revelation and Science, 2014)
It is a basic psychological premise that human being acts the way he thinks; in other words, our acts explain the way we think. This premise emphasizes the assumption that problems of Muslim societies are mainly result of the prevailing thoughts which in turn are production of education philosophies. Whitehead emphasizes that the mentality of an epoch springs from the view of the world, which is in fact, dominant in the educated sections of the community in question. Hence, the contemporary global crises, especially in the Muslim world, have shifted the attention once again to the question of education and initiated many studies on this topic. The proper understanding of such problems, however, might not be possible without understanding the underlying philosophy of education, which deals with the major educational questions about the recipient, the content, and goals of education. The objective of this paper is to highlight the education philosophy of International Islamic University Malaysia (IIUM) as an example of new model of Islamic education of higher learning that integrates knowledge with values and modernity with classic. The paper is designed to provide the basic information on IIUM philosophy, aiming at creating awareness on significance of this topic. It does not review or evaluate the theory of ‘Islamization and integration of knowledge’ (IOK); rather it presents the structure and the general framework of IIUM educational philosophy and its implications on practical challenges of modern Muslim societies in the globalizing world. This exposition would be in a historical context of Islamic education and development of its reformation thought.